The relationship between science teachers’ use of the flipped classroom strategy and their attitudes towards developing higher-order thinking skills among upper basic stage students in Hebron - Bostanje, Haneen Mahmoud Taha (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the relationship between science teachers' use of the flipped classroom strategy and their attitudes towards developing higher-order thinking skills among students of the higher basic stage in the Hebron governorate. In order to achieve the goal of the study, the researcher followed the descriptive and analytical approach, as she/he conducted a questionnaire to measure the extent to which science teachers use the flipped classroom strategy, and she conducted another questionnaire to measure the attitudes of science teachers towards developing higher-order thinking skills among students of the higher basic stage. Then, the two questionnaire sheets are electronically applied to a random sample of science teachers in the Hebron governorate. The number of the sample is (136) teachers in all directorates of the Hebron governorate.The results have shown that science teachers use the flipped classroom strategy frequently. Moreover, science teachers' attitudes towards developing higher-order thinking skills among students were at a high level, as the field of "critical thinking skills" came in the first place, followed by "problem-solving skills", however, "creative thinking skills" ranked last. Besides, the results have shown a strong correlation between science teachers ’use of the flipped classroom strategy and teachers' attitudes towards developing students' higher-order thinking skills. And, there are statistically significant differences in the science teachers' use of the flipped classroom strategy in teaching students of the higher basic stage in the Hebron governorate as well as in the science teachers' attitudes towards developing higher-order thinking skills among students of the higher basic stage in the Hebron governorate according to the gender variable for females, and according to the directorate variable for the directorate North Hebron.given the findings of the study; The researcher recommended that it is necessary to provide means of support to encourage teachers to employ modern technologies in teaching thinking. It is also necessary to conduct more studies dealing with the relationship between teachers' attitudes towards developing higher thinking skills and employing other teaching strategies and to conduct evaluation studies to examine the effectiveness of flipped learning strategies in teaching thinking.
Keywords: Higher-order thinking skills; Flipped classroom; Science; Higher basic stage